Evaluation of mechanical damage in concrete subjected to uniaxial compression and tensile by diametrical compression with longitudinal and transverse ultrasonic waves - ARAUJO,A. V. P. (2018)
Abstract In the research program both longitudinal and transverse ultrasonic waves were applied to concrete specimens under uniaxial compression and tensile diametrical compression. A total of 45 concrete specimens with five (5) different mixes were loaded until failure. While load was being applied - in compression and split tension - ultrasonic pulses were recorded and velocities calculated for both shear and pressure waves. The results indicate that longitudinal or transverse ultrasonic waves can be applied in the evaluation of diffuse damage (microcracking in uniaxial compression) or concentrated damage (tensile microcracking by diametrical compression) imposed on the concrete mechanically through the application of loads.